Effect of buffer layer on distortion and temperature in laser cladding. (2023) - Thawari, Nikhil; Gullipalli, Chaitanya; Gupta, T.V.K.
Abstract: Laser Cladding is an advance surface coating technique used to develop high wear, corrosion-resistant deposits. The cladding process involved rapid heating/cooling cycles, resulting in large thermal gradients which induces large residual stresses and substrate distortion affecting mechanical, microstructural properties as well as part performance. In the present work, a buffer layer of Inconel 625 is added prior to Stellite 6 hard laser cladding to investigate the role of intermediate layer deposition on distortion and temperature evolution. Further, the impact of process parameters on distortion is also evaluated. In-situ distortion and thermal history monitoring were performed using multiple non-contact displacement sensors and pyrometers, while depositing Stellite 6 and buffer layer. The post-process analysis is performed to find the correlation and role of intermediate layer on distortion development; and the results are further compared with direct multi-layer Stellite 6 cladding. The longitudinal bowing type of distortion is observed in both cases and found that deflection increases with increase in laser power. Online measurements reveal that samples with buffer layer addition result in the development of 15 - 20 % lower temperature and 22 - 30 % less distortion compared to direct Stellite 6 samples.